3D cell coculture tumor model: A promising approach for future cancer drug discovery. (March 2019) - Xin, Xin; Yang, Hopen; Zhang, Fengli; Yang, Shang-Tian
Highlights: Multiple stromal cell types play vital roles in tumor initiation, growth, and metastasis. Coculturing cancer and stromal cells can better mimic tumor microenvironment. In vitro studies of tumor-stromal cell interactions in cocultures are summarized. Application of 3D cocultures for high throughput screening of cancer drugs is discussed. Abstract: It is recognized that tumors do not exist and grow as isolated entities of neoplastic cells, but rather in continuous and bidirectional communication with adjacent stromal cells. Stromal cellular components, like fibroblasts, endothelial cells and multiple immune cells, have been proven to play critical roles in tumor development. In the past decade, a variety of in vitro three-dimensional (3D) tumor models were developed to replace conventional monolayer cell culture systems. 3D cell coculture between tumor and stromal cells has also gained increasing interest due to improved mimicry of in vivo tumor microenvironments. In this review, we first provide a general overview of the mechanisms for cancer development mediated by several key types of stromal cells, and their current applications in cell coculture. Next, a variety of current methodologies for 3D cell coculture are summarized in terms of cell contact methods, 3D scaffolds and culture devices. The potential of an integrated high throughput (HT) 3D cell coculture screening platform for cancer drug discovery is also discussed in this review.